Effect of planting time on the incidence of blast and false smut of rice in Haryana - RAM SINGH, D.S. DODAN and (Indian Phytopathology, 2002)
Blast caused by Pyricularia oryzae cav. accounts for serious yield losses on scented tall varieties in Haryana. Besides, false smut caused by Ustilaginoidea virens (Cke.) Tak. is also reported to cause huge loss in yield, in high yielding varieties in certain areas. The present study was undertaken to determine the effect of planting time on the incidence of neck blast and false smut.